JADID LITERATURE EXPONENTS - G‘aniyeva Nozanin G‘ayratovna (Лучшие интеллектуальные исследования, 2023)
Jadidism or jadidism (Arabic: ديدج jadīd — Yeni) is a socio — political, educational movement that was instrumental in the life of Turkistan, Caucasus, Crimea, Tataristan at the beginning of the 20th century in the late 19th century. Jadidism initially arose in the Crimea in the 80s of the XIX century. It spread in Central Asia from the 90s of the 19th century.